Business Mathematics CHAPTER 1 : Fundamental Concept of Mathematics Business Mathematics CHAPTER 1 : Fundamental Concept of Mathematics 1.2 Sequence ➢1.2.1 Arithmetic Sequence ➢1.2.2 Geometric Sequence ❖ A Sequence is a list of things (usually numbers) that are in order. 1st term 3, 5, 7, 9, … 2nd term 3rd term Three dots means goes on forever (infinite) 4th term (“term”, “element”, or “member” mean the same thing) 3 When the sequence goes on forever it is called an infinite sequence, otherwise it is a finite sequence 1, 2, 3, 4,... Is a very simple sequence (and it is an infinite sequence) 20, 25, 30, 35,... Is also an infinite sequence 1, 3, 5, 7 Is the sequence of the first 4 odd numbers (and is a finite sequnce) 4, 3, 2, 1 Is 4 to 1 backwards 1, 2, 4, 8, 16, 32,... Is an infinite sequence where every term doubles a, b, c, d, e Is the sequence of the first 5 letters alphabetically f, r, e, d Is the sequence of the letters in the name “fred” 0,1, 0, 1, 0, 1,... Is the sequence of alternating 0s and 1s (yes they are in order, It is an alternating order in this case ) 4 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, ... This is the Fibonacci Sequence The next number is found by adding the two numbers before it together: •The 2 is found by adding the two numbers before it (1+1) •The 21 is found by adding the two numbers before it (8+13) Rule is Tn = Tn-1 + Tn-2 That rule is interesting because it depends on the values of the previous two terms. Rules like that are called recursive formulas. The Fibonacci Sequence is numbered from 0 onwards like this : 𝑻𝒏 n= 0 1 2 3 4 5 6 7 8 9 10 11 12 13 14 … xn 0 1 1 2 3 5 8 13 21 34 55 89 144 233 377 … 5 A sequence usually has a Rule, which is a way to find the value of each term Example : the sequence { 3, 5, 7, 9, …} starts at 3 and jumps 2 every time : +2 +2 0 1 2 3 4 5 6 +2 7 8 +2 9 10 Saying "starts at 3 and jumps 2 every time" is fine, but it doesn't help us calculate the: 10th term, 100th term, or nth term, where n could be any term number we want. So, we want a formula with "n" in it (where n is any term number) 6 So, What Can A Rule For {3, 5, 7, 9, ...} Be? Test Rule : 2n n Term Test Rule 1 3 2𝑛 = 2 × 1 = 2 2 5 2𝑛 = 2 × 2 = 4 3 7 2𝑛 = 2 × 3 = 6 too low by 1 every time Test Rule : 2n + 1 n Term Test Rule 1 3 2𝑛 + 1 = 2 × 1 + 1 = 3 2 5 2𝑛 + 1 = 2 × 2 + 1 = 5 3 7 2𝑛 + 1 = 2 × 3 + 1 = 7 That Works! So instead of saying "starts at 3 and jumps 2 every time" we write this: 2n+1 7 8 In an Arithmetic Sequence the difference between one term and the next is a constant. Notation To make it easier to use rules, we often use this special style: 𝑻𝒏 term number term General Term a – first term • 𝑻𝒏 term number • n is the term number d – common difference First term 𝑇1 = a Second term 𝑇2 = a + d Third term 𝑇3 = a + 2d Fourth term 𝑇4 = a + 3d 𝑇𝑛 - nth term 9 Example : 1, 4, 7, 10, 13, 16, 19, 22, 25, … This sequence has a difference of 3 between each number. Its Rule is 𝑻𝒏= 3n - 2 In General we can write an arithmetic sequence like this: {a, a+d, a+2d, a+3d, ... } Tn = a + d(n-1) (We use "n-1" because d is not used in the 1st term). 10 Example : Write the Rule, and calculate the 4th term for 3, 8, 13, 18, 23, 28, 33, 38, … This sequence has a difference of 5 between each number. The value of a and d are : ▪ a = 3 (the first term) ▪ d = 5 (“the common difference”) The Rule can be calculated : Tn = a + d(n − 1) = 3 + 5(n − 1) = 3 + 5n − 5 = 5n − 2 So, the 4th term is : T4 = 5 4 − 2 = 18 11 Example 1 What is the fiftieth term of the arithmetic sequence 3, 7, 11, 15, …? A 53 B 151 C 199 D 203 This sequence has a difference of 4 between each pair of numbers. The values of a and d are : a = 3 (the first term) d = 4 (the “common difference”) The Rule can be calculated : Tn = a + d ( n − 1) = 3 + 4 ( n − 1) = 3 + 4n − 4 = 4n − 1 So, the 50th term is : T50 = 4 50 − 1 = 200 − 1 = 199 12 Example 2 What is the twentieth term of the arithmetic sequence 21, 18, 15, 12, …? A -39 B -36 C1 D 78 This sequence has a descending, so has a difference of -3 between each pair of numbers. The values of a and d are : a = 21 (the first term) d = -3 (the “common difference”) The Rule can be calculated : Tn = a + d ( n − 1) = 21 + ( -3 (n − 1) ) = 21-3n + 3 = 24 − 3n So, the 20th term is : T20 = 24 − 3 20 = 24 − 60 = −36 13 Example 3 When the first term of an arithmetic sequence is 4 and the tenth term is 67, what is the common difference? A 6 B 7 C 8 D 9 Let the first term be a and the common difference d Use the formula for the nth term : Tn = a + d(n − 1) The first term = 4 a = 4 equation (1) The tenth term = 67 T10 = a + d (10 − 1) = 67 67 = a + 9d = 67 equation ( 2 ) Substitute a = 4 from (1) into (2) 4 + 9d = 67 9d = 63 d = 63 9 = 7 The common difference is 7 14 Example 4 What is the thirty-second term of the arithmetic sequence -12, -7, -2, 3…? A 143 B 148 C 53 D 167 This sequence has a difference of 5 between each pair of numbers. The values of a and d are : a = -12 (the first term) d = 5 (the “common difference”) The Rule can be calculated : T5 = a + d(n − 1) = -12 + 5(n − 1) = -12 + 5n - 5 = 5n - 17 So, the 20th term is : T32 = 5 32 − 17 = 160 − 17 = 143 15 Example 5 The fifth term of an arithmetic sequence is 11 and the tenth term is 41. What is the common difference? A -19 B -13 C -9 D 6 Let the first term be a and the common difference d Use the formula for the nth term : Tn = a + d(n − 1) The fifth term = 4 T5 = a + d(5 - 1) = 11 a + 4d = 11 (1) The tenth term = 41 T10 = a + d(10 − 1) = 41 a + 9d = 41 (2 ) Substitute (1) from (2) a + 9d = 41 a + 4d = 11 − − − − − − − Subtract 5d = 30 so d = 30 5 = 6 Substitute d = 6 into (1) a + 4 6 = 11 a + 24 = 11 a = −13 The first term is -13 16 What to sum Go to this value 4 To sum up the terms of this arithmetic sequence: Start at this value n = 1 + 2 + 3 + 4 = 10 n-1 a + (a + d ) + (a + 2d ) + (a + 3d ) + ... n =1 (a + kd ) = (2a + (n − 1)d ) It says “Sum up n where n goes from 1 to 4, Answer = 10 k =0 (called Sigma ) means "sum up" 17 Each term is the same !, and there “ ” of them so … 𝟐𝐒 = 𝐧 × (𝟐𝐚 + 𝐧 − 𝟏 𝐝) Now, just divide by 2 and we get : n S= × 2a + n − 1 d 2 First, we will call the whole sum “S” : 𝐒 = 𝐚 + 𝐚 + 𝐝 + ⋯ + 𝐚 + 𝐧 − 𝟐 𝐝 + (𝐚 + 𝐧 − 𝟏 𝐝) n −1 n ( ) a + kd = (2a + (n − 1)d ) k =0 2 Next, rewrite S in reverse order : 𝐒 = 𝐚 + 𝐧 −𝟏 𝐝 + 𝐚 + 𝐧 − 𝟐 𝐝 + ⋯+ 𝐚 + 𝐝 +𝐚 Now add those two, term by term : S =a + (𝐚 + 𝐝) + ⋯ + (𝐚 + 𝐧 − 𝟐 𝐝) +(𝐚 + 𝐧 − 𝟏 𝐝) S = (𝐚 + 𝐧 − 𝟏 𝐝) + 𝐚 + 𝐧 − 𝟐 𝐝 + ⋯ + (𝐚 + 𝐝) +𝐚 __________________________________________________________________________ 2S = (𝟐𝐚 + 𝐧 − 𝟏 𝐝) + 𝟐𝐚 + 𝐧 − 𝟐 𝐝 + ⋯ + (𝟐𝐚 + 𝐧 − 𝟏 𝐝) +(𝟐𝐚 + 𝐧 − 𝟏 𝐝) 18 Example : Add up the first 10 terms of the arithmetic sequence : { 1, 4, 7, 10, 13, …} The values of a and n are : ❑ a = 1 (the first term) ❑ d = 3 (the “common difference”) between terms ❑ n = 10 (how many terms to add up) So n −1 n ( ) (2a + (n − 1)d ) a + kd = k =0 2 becomes 10 −1 10 ( ) (2 1 + (10 − 1) 3) 1 + k 3 = k =0 2 Example 6 What is the sum of the first sixteen term of the arithmetic sequence 1, 5, 9, 13, …? A 62 B 496 C 528 D 992 1, 5, 9, 13, … The values of a, d and n are : ❑ a = 1 (the first term) ❑ d = 4 (the “common difference”) between terms ❑ n = 16 (how many terms to add up) Use the formula Sn = n ( 2a + (n − 1) d) 2 16 ( 2 1 + 15 4 ) 2 = 8 ( 2 + 60 ) Therefore S16 = = 8 62 = 496 20 Example 7 What is the sum of the first thirty terms of the arithmetic sequence 50, 45, 40, 35, …? A -675 B 275 C 675 D 3,675 50, 45, 40, 35, … The values of a, d and n are : ❑ a = 50 (the first term) ❑ d = -5 (the “common difference”) between terms ❑ n = 30 (how many terms to add up) Use the formula Sn = n ( 2a + (n − 1) d) 2 30 ( 2 50 + 29 -5 ) 2 = 15 (100 − 145 ) Therefore S30 = = 15 −45 = -675 21 Example 8 What is the sum of the eleventh to twentieth terms (inclusive) of the arithmetic sequence 7, 12, 17, 22, …? A 154 B 295 C 795 D 1,090 7, 12, 17, 22, … The values of a, d and n are : ❑ a = 7 (the first term) ❑ d = 5 (the “common difference”) between terms To find the sum of the eleventh to twentieth terms we subtract the sum of the first ten terms from the sum of the first 20 terms So we use the formula Sn = n ( 2a + (n − 1) d ) twice to find S10 and S20 2 10 (2 7 + (10 − 1) 5) = 5(14 + 45) = 5 59 = 295 2 20 (2 7 + (20 − 1) 5) = 10(14 + 95) = 10 109 = 1,090 S20 = 2 S10 = Therefore the sum of the eleventh to twentieth terms = 1,090 – 295 = 795 22 Example 9 The eleventh term of arithmetic sequence is 30 and the sum of the first eleven terms is 55. What is the common difference? A 5 B6 C 8 D 10 The eleventh term , T11 = a + d (11 − 1) (Equation1) a + 10d = 30 11 ( 2a + (11 − 1) d) 2 11 55= ( 2a + 10d ) (Equation 2) 2 55=11( a + d ) The sum of the first eleven terms, 55= 5=a + 5d Subtract (Equation 2) from (Equation 1) Let the first term be a and the common difference d Use the formula for the n’th term : Tn = a + d(n − 1) and the formula for the sum to n terms Sn = n (2a + (n − 1)d ) 2 a + 10d = 30 a + 5d = 5 Subtract 5d = 25 So d = 25 ÷ 5 = 5 23 Business Mathematics CHAPTER 1 : Fundamental Concept of Mathematics 25 Geometric Sequences In a Geometric Sequence each term is found by multiplying the previous term by a constant. Example : 2, 4, 8, 16, 32, 64, 128, 256, … This sequence has a factor of 2 between each number. Its Rule 𝑻𝒏 = 𝟐 𝒏 In General we can write a geometric sequence like this: {a, ar, ar2, ar3, ... } where: •a is the first term, and •r is the factor between the terms (called the "common ratio") Note : r should not be 0 • when r = 0, we get the sequence {a, 0, 0, …} which is not geometric 26 Example : 10, 30, 90, 270, 810, 2430, … This sequence has a factor of 3 between each number. The values of a and r are : • a = 10 (the first term) • r = 3 (the “common ratio”) The Rule for any term is : Tn = 10 3(n −1) So, the 4th term is : T4 = 10 3(4-1) = 10 33 = 10 27 = 270 and the 10th term is : T10 = 10 3(10-1) = 10 39 = 10 19683 = 196830 27 Tn = ar(n-1) (We use "n-1" because ar0 is the 1st term) Example : A geometric sequence can also have smaller and smaller values : Example : {1, 2, 4, 8, …} 4, 2, 1, 0.5, 0.25, … The sequence starts at 1 and doubles each time, so The sequence has a factor of 0.5 (a half between each number.) • a = 1 (the first term) • r = 2 (the “common ratio” between terms is a doubling) Its Rule is T4 = 4 (0.5) n −1 And we get : a, ar, ar 2,ar 3,... = 1, 1 2, 1 22 , 1 23 ,... = 1, 2, 4, 8,... 28 Example 10 What is the eleventh term of the geometric sequence 3, 6, 12, 24, …? A 66 B 768 C 1536 D 3072 This sequence has factor of 2 between each pair of numbers. The values of a and r are : • a = 3 (the first term) • r = 2 (the “common ratio”) The Rule for any term is : Tn = ar n -1 Therefore, T11 = 3 210 = 3 1024 = 3072 29 Example 11 1 What is the ninth term of the geometric sequence 81, 27, 9, 3, …? A C 1 81 1 243 B 1 27 D 1 This sequence has a factor of 3 between each pair of numbers. The value of a and r are : ▪ a = 81 (the first term) 1 ▪ r = (the “common ratio”) 3 9 The Rule for any term is : Tn = ar (n −1) Therefore 𝑇𝑛 8 1 T9 = 81 3 1 = 81 6561 81 = 6561 1 = 81 30 Example 12 The first term of a geometric sequence is 5 and their sixth term is 160. What is the common ratio? A 0.5 B2 C 3 D4 Let the first term be a and the common ratio r We know the first term a = 5 Use the formula for the n’th term : Tn = ar n −1 T6 = ar 6−1 The sixth term = 160 ar 5 = 160 When a = 5 Therefore, 5r 5 = 160 r 5 = 160 5 = 32 r = 5 32 =2 31 Example 13 The fourth term The fourth term of a geometric sequence is 27 and the seventh term is 1. What is the first term? 1 A 3 B 81 C 243 D 729 T4 = ar 4−1 = 27 ar 3 = 27 equation (1) The seventh term T7 = ar 7−1 = 1 ar 6 = 1 equation ( 2 ) Divide (2) by (1) 1 27 1 r= 3 1 Substitute r = into equation (1), 3 r3 = Let the first term be a and the common ratio r 3 Use the formula for the n’th term : Tn = ar n −1 1 a× = 27 3 1 a× = 27 27 a = 27×27 = 729 The first term is 729 32 First, call the whole sum “S” : S = a + ar + ar 2 + ... + ar (n − 2 ) + ar (n −1) Equation 1 Next, multiply S by r : S r = ar + ar 2 + ar 3 + ... + ar (n−1) + ar n Equation 2 S = a + ar + ar 2 + ... + ar (n −1) - S r = − ar − ar 2 − ... − ar (n −1) − ar n ______________________________ S - S r = a − ar n S - S r = a - ar n Factor out S and a : 𝑆 1 − 𝑟 = 𝑎(1 − 𝑟 𝑛 ) Divide by 1 − 𝑟 ∶ 𝑆 = 𝑎(1−𝑟 𝑛 ) (1−𝑟) 1− rn ar = a 1− r ( ) n −1 k k =0 Well … when r is less than 1, then 𝑟 𝑛 goes to zero and we get : 1 ( ) ar = a 1− r k k =0 33 Summing a Geometric Series When we need to sum a Geometric Sequence, there is a handy formula. To sum: a + ar + ar2 + ... + ar(n-1) Each term is ark, where k starts at 0 and goes up to n-1 1− rn ar = a 1− r ( ) n −1 k k =0 a is the first term r is the "common ratio" between terms n is the number of terms 34 R must be between ( but not including) -1 and 1 and r should not be 0 because we get the sequence {a, 0, 0, …} which isn’t geometric Example : Add up ALL the terms of the Geometric Sequence that halves each time : 1 1 1 1 , , , ,... 2 4 8 16 We have : 1 ▪ a = 2 ( the first term ) 1 ▪ r = 2 ( halves each time) 1 1 k 1 1 = 2 1 k =0 2 2 1− 2 1 1 2 = =1 1 2 1 1 1 Yes … adding (2)+(4)+(8)+… equals exactly 1. 35 Example : Sum the first 4 terms of 10, 30, 90, 270, 810, 2430, … This sequence has a factor of 3 between each number. The values of a, r and n are : ▪ a = 10 ( the first term ) ▪ r = 3 ( the “common ratio” ) ▪ n = 4 (we want to sum the first 4 terms) So 1− rn ar = a 1− r ( ) n −1 k k =0 becomes 1 − 34 = 400 10 3 = 10 k =0 1− 3 4 −1 ( k ) You can check it yourself : 10 + 30 + 90 + 270 = 400 And, yes, it is easier to just add them in this example, as there are only 4 terms. But imagine adding 50 terms … then the formula is much easier 36 Example : … doubling the grains of rice on each square … … how many grains of rice in total? So we have : • a = 1 (the first term) • r = 2 (doubles each time) • n = 64 (64 squares on a chess board) 1− rn ar = a 1− r ( ) n −1 k k =0 1 − 264 ar = 1 k =0 1− 2 1 − 264 = -1 = 264 − 1 = 18, 446, 744, 073, 709, 551, 651 64 −1 ( ) k On the page Binary Digits we give an example of grains of rice on a chess board. The question is asked : When we place rice on a chess board : ▪ 1 grain on the first square, ▪ 2 grains on the second square, ▪ 4 grains on the third and so on, 37 Example 14 What is the sum of the first eight term of the geometric sequence 5, 15, 45, …? A 320 B 5465 C 16400 D 32800 r n −1 Use the formula Sn = a r −1 38 − 1 Therefore, Sn = 5 3 −1 6561 − 1 = 5 3 −1 = 5 6560 2 = 16400 5, 15, 45, … This sequence has a factor of 3 between each pair of number. The values of a, r and n are : ▪ a = 5 ( the first term ) ▪ r = 3 ( the “common ratio” ) ▪ n = 8 (we want to sum the first 8 terms) 38 Example 15 What is the ninth term of the geometric sequence : 1 − 1 1 − 1 , , , ,... 3 9 27 81 A 1 2 B 4 9 C 1 3 D 1 4 1 − 1 1 − 1 , , , ,... 3 9 27 81 We known : 1 ▪ a = 3 (the first term) ▪ r= −1 3 (the “common ratio”) Use the formula for the sum to infinity of a geometric sequence : 1 S = a 1- r Therefore, 1 3 S9 = −1 1− 3 1 1 4 = 3 = 4 3 3 3 1 = 4 39 Example 16 What is the sum of the first nine terms of the geometric sequence 20, 10, 5, …? Give your answer as a decimal correct to 1 decimal place. A 39.9 B 40.0 C 59.9 D 79.8 20, 10, 5, … 1 - rn Use the formula Sn = a 1- r 1 9 1− 2 Therefore, S9 = 20 1 1 2 1 1− 512 = 20 1 1 2 511 1 512 2 511 1 = 20 512 2 2555 = 64 = 39.9 to 1 decimal place = 20 1 This sequence has a factor of 2 between each pair of numbers. The values of a, r and n are : ▪ a = 20 ( the first term ) 𝟏 ▪ r = 𝟐 ( the “common ratio” ) ▪ n = 9 (we want to sum the first 9 terms) 40 Business Mathematics CHAPTER 1 : Fundamental Concept of Mathematics 2.1 Simple Interest 2.1.1 Introduction to Interest 2.1.2 Simple Interest Formula – Years or Months 42 Interest: how much is paid for the use of money (as a percent, or an amount) How Much does it Cost to Borrow Money? Different places charge different amounts at different times! Money is Not Free to Borrow People can always find a use for money, so it costs to borrow money. But they usually charge this way As a percent (per year) of the amount borrowed It is called INTEREST 43 Example: Amir Borrow RM1,000 from the Bank Amir wants to borrow RM1,000. The local bank says "10% Interest". So to borrow the RM1,000 for 1 year will cost: RM1,000 × 10% = RM100 In this case the "Interest" is RM100, and the "Interest Rate" is 10% TODAY NEXT YEAR RM1000 RM1000 Amir Bank Amir Bank RM100 interest Amir Borrows RM1,000, but has to pay back RM1,100 Note : I am showing a full year loan, but banks often want you to pay back the loan in small monthly amounts, and they also charge extra fees too! 44 principal borrower TODAY NEXT YEAR RM1000 RM1000 Amir Lender Bank The Loan Amir Bank RM100 interest The Repayment Amir is the Borrower, the Bank is the Lender The Principal of the Loan is RM1,000 The Interest is RM100 The important part of the word “Interest” is Inter-meaning between (we see interin words like interior and interval), because the interest happens between the start and end of the loan. 45 Example: Amir borrows RM1,000 for 5 Years, at 10% simple interest: Example: Amir borrows RM1,000 for 7 Years, at 6% simple interest: • Interest = RM1,000 × 10% x 5 Years = RM500 • Plus the Principal of RM1,000 means Amir needs to pay RM1,500 after 5 Years • Interest = RM1,000 × 6% x 7 Years = RM420 • Plus the Principal of RM1,000 means Amir needs to pay RM1,420 after 7 Years 46 There is a formula for simple interest I = Prt where ❖ ❖ ❖ ❖ I = interest P = amount borrowed (called “Principal”) r = interest rate t = time Example : Ila borrowed RM3000 for 4 years at 5% interest rate, how much interest is that? I = Prt I= RM3,000 × 5% × 4 years I = RM3000 × 0.05 × 4 I = RM600 47 Example 17 Jerry borrowed RM4000 for 5 years at 6% simple interest rate. How much interest is that? A RM800 B RM1000 C RM1200 D RM1500 where ❖ ❖ ❖ ❖ I = interest P = Principal = RM400 r = interest rate = 6% = 0.06 t = time = 5 years I = RM4000 × 0.06 × 5 = 1200 Use I = Prt where ❖ ❖ ❖ ❖ I = interest P = amount borrowed (called “Principal”) r = interest rate t = time 48 Example 18 Jerry borrowed RM7000 at a simple interest rate of 3% per year. After a certain number of years he had paid RM840 in interest altogether. How many years was that? A 2 years C 1 32 Use years B 3 years D 4 years ❖ ❖ ❖ ❖ I = interest = RM840 P = Principal = RM7000 r = interest rate = 3% = 0.03 t = time So, 840 = 7000 × 0.03 × t Simplify : 840 = 210 × 𝑡 Rearrange : 𝑡 = 840 ÷ 210 Solve : t = 4 I = Prt where ❖ ❖ ❖ ❖ where I = interest P = amount borrowed (called “Principal”) r = interest rate t = time The time was 4 years 49 Example 19 Sam borrowed RM4500 for 2 years and had to pay RM630 at a simple interest at the end of that time. What rate of interest did he pay? A 6% B 7% C 8% D 9% Use where ❖ ❖ ❖ ❖ I = interest = RM630 P = Principal = RM4500 r = interest rate t = time = 2 years So, 630 = 4500 × r × 2 Simplify : 630 = 9000 × 𝑟 Rearrange : r= 630 ÷ 9000 Solve : r = 0.07 = 7% I = Prt where ❖ ❖ ❖ ❖ I = interest P = amount borrowed (called “Principal”) r = interest rate t = time 50 Example 20 1 Julie borrowed RM3500 for 3 years at 7 % annual 2 simple interest rate. How much interest is that? A RM375 B RM787.50 C RM810 D RM812.50 where ❖ ❖ ❖ ❖ I = interest P = Principal = RM350 1 r = interest rate = 7 2% = 0.075 t = time = 3 years Therefore, I = RM3500 × 0.075 × 3 = 787.50 Use I = Prt where ❖ ❖ ❖ ❖ I = interest P = amount borrowed (called “Principal”) r = interest rate t = time 51 Example 21 Dan borrowed RM2000 for 6 month at 12% annual simple interest rate. How much interest is that? A RM120 B RM144 C RM1200 D RM1440 where ❖ ❖ ❖ ❖ I = interest P = Principal = RM2000 r = interest rate = 12% = 0.12 t = time = 6 month = 0.5 year I = RM200 × 0.12 × 0.5 = RM120 Use I = Prt I=RM2000 where ❖ ❖ ❖ ❖ I = interest P = amount borrowed (called “Principal”) r = interest rate t = time 52 53